Overview of Entrepreneurship Education for Students - Bahri, Efri Syamsul (Perkumpulan Psikologi Transformasi Indonesia (P2TI), 2024)
The minimum number of entrepreneurs in developed countries is 4%. This research aims to conduct a review of entrepreneurship education for students. This research uses qualitative methods with a descriptive approach and a literature study. Data was obtained from reference literature on the open-access platform. The results of this research show that there are six indicators of entrepreneurship education's success: entrepreneurial character, an environment that follows entrepreneurial values, an environment that has an entrepreneurial nuance, the desire to become an entrepreneur, increased knowledge of entrepreneurship, and business opportunities. The government and universities need to support the implementation of entrepreneurship education for students as a contribution to realizing Indonesia as a developed country.